Analisis Skala Kematangan Perilaku Beragama pada Siswa Sekolah Menengah Pertama Berasrama - Abdurahim Casim (Journal of Innovative Counseling : Theory, Practice, and Research, 2019)
This study aims to describe the maturity of religious behavior in adolescents, especially boarding junior high school students. There are three aspects that are seen from the maturity of religious behavior in adolescents, namely aspects of thoughts, feelings and actions. Based on the analysis of the relevant literature, this study developed 111 items that describe the maturity of religious behavior in adolescents. The sample of this study was 230 students of grade IX boarding school. Item validity and reliability are measured by IBM SPSS Statistics 25. The result, 1) Pearson Product Moment 2-Tailed Correlation produces 107 items declared valid and only 4 items are invalid; and 2) Cronbach's Alpha (?) reliability coefficient is 0.96 which means very high. The collected data is then analyzed using descriptive statistical analysis. The results of the analysis obtained information that in general the aspects and indicators of maturity of religious behavior in adolesce